2020
DOI: 10.4103/jcar.jcar_3_20
|View full text |Cite
|
Sign up to set email alerts
|

Myofibroblasts as important diagnostic and prognostic indicators of oral squamous cell carcinoma: An immunohistochemical study in normal oral mucosa, epithelial dysplasia, and oral squamous cell carcinoma

Abstract: BACKGROUND: Cancer invasion is a critical step for tumor growth and its progression. The focus on epithelial changes is shifting to increasing recognition that the microenvironment makes significant contributions to tumor progression. Stromal myofibroblasts play an important role in tumor invasion and metastasis due to its ability to modify the extracellular matrix. Based on this literary evidence, we carried out an immunohistochemical study to observe the expression of myofibroblasts in oral epit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Since myofibroblasts are cancer-induced host cells, numerous studies have demonstrated the significance of stromal components in tumor genesis, growth, invasion, and aggressiveness. [ 20 21 22 ] In a similar study carried out by Shete et al .,[ 23 ] authors have reported significantly higher expression of myofibroblasts in patients with carcinoma in comparison with healthy controls. They concluded that genetically altered epithelium (malignant epithelium) might have an inductive impact on the adjacent stroma to produce myofibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Since myofibroblasts are cancer-induced host cells, numerous studies have demonstrated the significance of stromal components in tumor genesis, growth, invasion, and aggressiveness. [ 20 21 22 ] In a similar study carried out by Shete et al .,[ 23 ] authors have reported significantly higher expression of myofibroblasts in patients with carcinoma in comparison with healthy controls. They concluded that genetically altered epithelium (malignant epithelium) might have an inductive impact on the adjacent stroma to produce myofibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study conducted by Shete MV et al . [ 17 ] in 2020, authors tried to relate the role of myofibroblasts in oral premalignant disorders, OSCC cases and healthy controls. They concluded that a-SMA expression in the mesenchyme component of OSCC patients was significantly enhanced in comparison to its expression in epithelial dysplasia and normal oral mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with leukaemia, increased expression of miR-200c/141 and miR-181a/181b through down regulation of TGFB signalling pathway is clearly related to increased WBC count and poorer prognosis ( 19 , 25 , 26 ). In patients with leukaemia, clonal arrest of B cells occurs in the G0/G1 phase of the cell cycle, associated with clonal proliferation of B cells.…”
Section: Introductionmentioning
confidence: 99%